Macromol. Rapid Commun. 8/2017. Issue 8 (19th April 2017) - Tan, Qinglong; Lu, Shanfu; Si, Jiangju; Wang, Haining; Wu, Chunxiao; Li, Xianfeng; Xiang, Yan
Abstract : Front Cover: Non‐ionized polymers with bunch‐like tertiary amine groups are successfully designed for vanadium redox flow batteries (VRFBs) The tertiary amine groups simultaneously act as ionic conductor for proton hopping and vanadium ion transport obstacles, leading to an impressive battery performance. Further details can be found in article number 1600710 by Qinglong Tan, Shanfu Lu, Jiangju Si, Haining Wang, Chunxiao Wu, Xianfeng Li, and Yan Xiang*.